Uterine rupture - Pinedo Reátegui, Adolfo (2015)
21 cases of uterine rupture occurred occurred in a span of 15 years with an incidence of 1 / 2,817 births. 18 cases occurred in patients with a history of cesarean section and only found 3 cases of uterine rupture with intact uterus. In 15 cases (72%) blood transfusion 500-4500 cc of whole blood is required. Dehiscence was incomplete in 14 cases and completed in 4 cases. The treatment of choice in 72% of cases was debridement and suture. We found 12 fetal deaths (57%) distributed in 10 stillbirths and neonatal deaths 2. There was a maternal death.